Analyzing Maxim Violations in the Batman Cartoon Movie - Nainggolan, Billi Andara; Rezeki, Indah Sri; Karlinda, Berti; Zulianti, Hajjah; Hastomo, Tommy (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This research aimed to define the types of maxims that are flouted in the Batman movie, to disclose and explain the implicature behind the characters' conversations, and to describe the reason for maxim flouting by the characters in the movie. Descriptive qualitative methodology was used in conjunction with a pragmatic approach in the current research. The research data were utterances containing maxim flouting spoken by characters in Batman: Under the Red Hood. The movie dialogues served as the context for the inquiry. This study's data source was the film Batman: Under the Red Hood. The data was gathered by downloading, watching, and then collecting the movie. The data is analyzed by categorizing it into several categories, such as maxim flouting, analyzing it, confirming or validating that the data is accurate, and then coming to a conclusion. The data were triangulated by consulting with the lecturers and applying theoretical triangulation to assure their trustworthiness. The results of the research are as follows. First, all types of maxim flouting are found in the movie. Second, the maxim of conversation flouted by the characters has implied meaning. Third, there are various reasons why the flouting maxim occurred in the movie, such as covering something, giving more information, changing the topic, and intriguing the listener. The flouting maxims occur for different reasons and meanings in this movie